The effect of implementing Postnatal Yoga on accelerating the physical recovery of postpartum mothers in the Payung Sekaki Community Health Center Work Area, Pekanbaru: The effect of implementing Postnatal Yoga on accelerating the physical recovery of postpartum mothers in the Payung Sekaki Community Health Center Work Area, Pekanbaru - Sellia Juwita (LPPM Universitas Abdurrab, 2026)
Background: The postpartum period is a period that begins after the placenta is born until six weeks postpartum, which is characterized by the process of restoring the reproductive organs and the mother's body system to pre-pregnancy conditions. Postnatal yoga is a form of complementary therapy that is increasingly used in postpartum maternal health services. Postnatal yoga combines breathing exercises, stretching, muscle strengthening, relaxation, and meditation that are adapted to the condition of the mother after giving birth. Objective: This study aims to analyze the effect of implementing Postnatal Yoga on accelerating the physical recovery of postpartum mothers in the Payung Sekaki Community Health Center Work Area, Pekanbaru. Method: This study uses a quantitative analytical method with a Quasi Experiment approach. The study was conducted in the Payung Sekaki Community Health Center work area, Pekanbaru City. The sample consisted of 42 breastfeeding mothers selected using the Accidental Sampling technique. Statistical tests used the independent T Test. Results: The average physical recovery time in the intervention group (5.14 days) was faster than the control group (7.48 days). The results of the Independent Sample T-Test showed a t-value of -8.479 with a significance value of p = 0.000. Because the p value <0.05. Conclusion: This study shows that postnatal yoga classes are statistically proven to be effective in accelerating the physical recovery period of postpartum mothers by 2.34 days faster than mothers who do not participate in postnatal yoga.